2014
DOI: 10.1155/2014/627434
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ADMA/DDAH Pathway after Hepatic Ischemia/Reperfusion Injury in Rats: The Role of Bile

Abstract: We investigated the effects of hepatic ischemia/reperfusion (I/R) injury on asymmetric dimethylarginine (ADMA, a nitric oxide synthase inhibitor), protein methyltransferase (PRMT) and dimethylarginine dimethylaminohydrolase (DDAH) (involved, resp., in ADMA synthesis and degradation), and the cationic transporter (CAT). Male Wistar rats were subjected to 30 or 60 min hepatic ischemia followed by 60 min reperfusion. ADMA levels in serum and bile were determined. Tissue ADMA, DDAH activity, DDAH-1 and CAT-2 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…While ADMA acts as a competitive inhibitor of the NOS, SDMA is a competitor of arginine transport but does not interfere with NOS [8]. Thus, an elevated serum ADMA level results in lowered NO levels, which leads to vasoconstriction, augmented thrombocyte aggregation, and cell adhesion to the endothelium and promotes proliferation of vascular muscle cells [9]. ADMA is metabolized to citrulline and dimethylamine by the enzyme dimethylarginine dimethylaminohydrolase (DDAH) and a small fraction is renally excreted whereas SDMA is almost entirely eliminated by the kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…While ADMA acts as a competitive inhibitor of the NOS, SDMA is a competitor of arginine transport but does not interfere with NOS [8]. Thus, an elevated serum ADMA level results in lowered NO levels, which leads to vasoconstriction, augmented thrombocyte aggregation, and cell adhesion to the endothelium and promotes proliferation of vascular muscle cells [9]. ADMA is metabolized to citrulline and dimethylamine by the enzyme dimethylarginine dimethylaminohydrolase (DDAH) and a small fraction is renally excreted whereas SDMA is almost entirely eliminated by the kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…CAT-2B is a low-capacity transporter and demonstrates high affinity to cationic amino acids, particularly ADMA (Closs et al, 1997). The liver takes up the most amounts of ADMA from serum and metabolizes it, mediated by particularly DDAH1 (Ferrigno et al, 2014). It was detected in a study by Siroen et al that patients with preoperative liver transplantation had higher levels ADMA when compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The liver metabolizes ADMA particularly by dimethylarginine dimethylaminohydrolase 1 (DDAH1). Beside this, ADMA may also be drained through the bile duct (Ferrigno et al, 2014) and broken down to α-keto-d-(N,N-dimethylguanidino)valeric acid by alanine glyoxylate aminotransferase 2 (Vallance and Leiper, 2004;Rodionov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental and clinical studies have evaluated the handling of ADMA and SDMA by the body, but their metabolic fate is not fully understood. ADMA and SDMA can be detected in plasma, urine, cerebrospinal and bronchoalveolar fluids ; we recently reported that ADMA is also secreted in bile and a time‐dependent increase of ADMA occurs during hepatic I/R injury .…”
mentioning
confidence: 99%